POTRET PEMANFAATAN ARCHITECTURE ENTERPRISE PERGURUAN TINGGI DI INDONESIA - Lathifah -; R. Teduh Dirgahayu; Handson Prihantoro (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2017)
Architecture enterprise in the current have an important role and Very broad one of them is in the colleges. Colleges consider the importance of Architecture enterprise for align information technology with business processes in academic information systems. The use of architecture enterprise is needed to be used as guidelines and reference a model that can be used a long period of time consistent with the needs and can be used optimally. Research take a portrait the use of architecture enterprise from three colleges is X University, Y University, and Y University. The data taken from interviews and surveys are processed into instruments. Instrument making still refers to previous research which resulted in 20 instruments, so that making it easier to measure four business architecture enterprise processes using TOGAF. Validation results using the process of explanatory statistics and speakers, so that the portrait utilization of architecture enterprise in college has an average of 2.60. Portrait utilization of architecture enterprise can be formulated into 3 research object that is application of architecture enterprise, influence of architecture enterprise, and business process of architecture enterprise which is documented to 3 universities, it can be concluded that enterprise architecture is almost always used for academic information system can be integrated well. But the academic information system that runs not all centralized into one, so that the documentation process isn’t well managed and when the University having trouble there aren't guidelines that can be used as a reference when doing every action. Academic information system made currently is still used in the short period because the existing applications and infrastructure only in accordance with the needs.